Subtype-specific actions of β-amyloid peptides on recombinant human neuronal nicotinic acetylcholine receptors (α7, α4β2, α3β4) expressed in Xenopus laevis oocytes - Pym, L; Kemp, M; Raymond-Delpech, V; Buckingham, S; Boyd, C; Sattelle, D (2005)
1 Two-electrode voltage-clamp electrophysiology has been used to study the actions of two amyloid peptides (Aβ 1-42, Aβ 1-40) on α7, α4β2 and α3β4 recombinant human neuronal nicotinic acetylcholine receptors (nicotinic AChRs), heterologously expressed in Xenopus laevis oocytes. 2 The application of Aβ 1-42 or Aβ 1-40 (1 pM-100 nM) for 5 s does not directly activate expressed human α7, α4β2 or α3β4 nicotinic AChRs. 3 Aβ 1-42 and Aβ 1-40 are antagonists of α7 nicotinic AChRs. For example, 10 nM Aβ 1-42 and Aβ 1-40 both reduced the peak amplitude of currents recorded (3 mM ACh) to 48±5 and 45±10% (respectively) of control currents recorded in the absence of peptide. In both the cases the effect is sustained throughout a 30 min peptide application and is poorly reversible. 4 Aβ 1-42 and Aβ 1-40 (10 nM) enhance currents recorded in response to ACh (3 mM) from oocytes expressing α4β2 nicotinic AChRs by 195±40 and 195±41% respectively. This effect is transient, reaching a peak after 3 min and returning to control values after a 24 min application of 10 nM Aβ 1-42. We observe an enhancement of 157±22% of control ACh-evoked current amplitude in response to 100 nM Aβ 1-42 recorded from oocytes expressing α4β2 nicotinic AChRs. 5 Aβ 1-42 and Aβ 1-40 (10 nM) were without antagonist actions on the responses of α3β4 nicotinic AChRs to ACh (1 nM-3 mM). © 2005 Nature Publishing Group All rights reserved.